Bagaeen, Samer y Clark, Celia (eds.) (2016). Sustainable Regeneration of Former Military Sites - Camerin, Federico (Documents d'Anàlisi Geogràfica, 2018)
Bagaeen, Samer y Clark, Celia (eds.) (2016) Sustainable Regeneration of Former Military Sites Londres y Nueva York: Routledge Research in Planning and Urban Design, 226 p. ISBN 978-11-380-1652-1